Exploration of Self-Efficacy and Entrepreneurial Motivation on MSME Performance in Malang City: A Qualitative Study - Fatmasari Endayani; Ernita Dian; Saman Saman (Management Dynamics: International Journal of Management and Digital Sciences, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy but face significant challenges in maintaining consistent and sustainable performance amidst changing market dynamics. This study aims to explore how self-efficacy and entrepreneurial motivation influence MSME performance in Malang City using an exploratory phenomenological qualitative approach. Twelve informants with at least two years of business experience and active operations were selected through purposive sampling. Data were collected through semi-structured interviews, analyzed using an inductive approach, and processed until data saturation was reached. The study found that MSME actors' self-efficacy is shaped by accumulated real experiences, including both successes and failures, which contribute to meaningful learning. Entrepreneurial motivation rooted in personal values was found to be stronger and more enduring than extrinsic motivation. The study identified a cyclical interaction between self-efficacy and motivation, reinforcing each other in fostering adaptive entrepreneurial behavior. Additionally, external factors such as family support, entrepreneurial communities, and government programs play a significant role in sustaining these psychological factors. This research contributes to entrepreneurship literature and offers practical recommendations for stakeholders to design more holistic MSME empowerment programs with tangible impact.